Simplified modelling of in-plane behaviour of masonry infilled RC frames under seismic loading: advantages and barriers - Hossameldeen Mohamed (2018)
Due to the significant contribution of the infill walls on the global seismic response of reinforced concrete (RC) buildings, several studies were carried out over time in order to identify this contribution. These studies led to the development of several models to simulate realistically the interaction between the infill and the adjacent RC frame. Due to the larger variety of masonry properties, several models can be found in the literature and these proposals are seen to be different in terms of their modelling refinement. The various techniques available to model the in-plane behaviour of infills are addressed, highlighting their application feasibility. Due to their low computational effort, the use of strut elements to model the behaviour of infill panels is a popular approach and several proposals are discussed in more detail. The reliability of using a strut model to simulate the infill panel behaviour is discussed based on experimental data from ten different test campaigns. In light of this comparison, several recommendations in terms of the characteristics of the strut models that need to be considered to achieve more realistic results when analysing the behaviour of masonry-infilled RC frame structures were established.